2012
DOI: 10.1080/09540121.2012.687823
|View full text |Cite
|
Sign up to set email alerts
|

Internet-using men who have sex with men would be interested in accessing authorised HIV self-tests available for purchase online

Abstract: Men who have sex with men (MSM) recruited in sex venues have been shown to be interested in accessing HIV home-tests if reliable and authorised tests were available. To what extent is this true for MSM recruited online? In an online survey in French on the use of unauthorised HIV home-tests purchased online, MSM previously unaware of the existence of these tests were asked if they would be interested in accessing them if these tests were authorised. Among 5908 non-HIV positive respondents, 86.5% expressed inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
1

Year Published

2013
2013
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 14 publications
3
48
0
1
Order By: Relevance
“…Although opinions about HIV self-testing have also been approached in feasibility HIV self-tests [35,37,38] and preference for HIV testing options studies [39][40][41][42], as far as we know, there are only a few publications focused on this topic, those of recent years yielding encouraging results. In Europe there is only one similar published study in France [43], showing that 86.5 % of non-HIV positive respondents, ''were interested in accessing an authorized self-test for purchase online''; aside from a British abstract presented at the 17th Annual Conference of the British HIV Association, reporting that 77 % of all non-HIV positive respondents ''believed home testing should be legalized and regulated'' and 62 % ''would consider to use it in the future'' [44]. There are two studies performed in the US during the last years; one compared the percentage of never tested MSM with a strong intention to use an over-the-counter rapid test who were somewhat unlikely to test in the next year (47.4 %) with those somewhat likely (76.5 %; OR 3.62; CI 2.39-5.49) and those very likely (85.6 %; OR 6.60; CI 4.09-10.66) [45]; the other study concentrated on black MSM and the results showed that prior to having sex, 66 % HIV-negative MSM would take an HIV test if their partner asked and 65 % would ask the partner to take it [46].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Although opinions about HIV self-testing have also been approached in feasibility HIV self-tests [35,37,38] and preference for HIV testing options studies [39][40][41][42], as far as we know, there are only a few publications focused on this topic, those of recent years yielding encouraging results. In Europe there is only one similar published study in France [43], showing that 86.5 % of non-HIV positive respondents, ''were interested in accessing an authorized self-test for purchase online''; aside from a British abstract presented at the 17th Annual Conference of the British HIV Association, reporting that 77 % of all non-HIV positive respondents ''believed home testing should be legalized and regulated'' and 62 % ''would consider to use it in the future'' [44]. There are two studies performed in the US during the last years; one compared the percentage of never tested MSM with a strong intention to use an over-the-counter rapid test who were somewhat unlikely to test in the next year (47.4 %) with those somewhat likely (76.5 %; OR 3.62; CI 2.39-5.49) and those very likely (85.6 %; OR 6.60; CI 4.09-10.66) [45]; the other study concentrated on black MSM and the results showed that prior to having sex, 66 % HIV-negative MSM would take an HIV test if their partner asked and 65 % would ask the partner to take it [46].…”
Section: Discussionmentioning
confidence: 91%
“…and also with the fact that it contributes to take responsibility for one's own health. Aspects such as privacy and anonymity described as the third most frequent reason in the French study [43], named in several diagnostic service preferences [42,49] and HIV self-test studies [12,27] and frequently pointed out as an advantage for introducing self-testing [18,50], were deemed much less important. However, this finding is not striking when knowing that attenders exposed themselves to being tested in the highly visible settings chosen by the diagnostic program and have ranked in similar order their preferences about characteristics they value most in an HIV testing service [36].…”
Section: Discussionmentioning
confidence: 99%
“…Pilot studies in Malawi and Kenya have demonstrated generally high acceptability among health workers and the general populations [11,12], along with high accuracy of self-testing with HIV RDTs that use oral fluid, when combined with a demonstration step and illustrated instructions [11,16,17]. In the USA, France and Australia, acceptability of targeted HIVST is reportedly high among men who have sex with men [19][20][21]. There have been only limited studies on unsupervised HIVST in resource-limited settings [8,12].…”
mentioning
confidence: 99%
“…Among those who had never been tested for HIV, 86% of those likely to get a test in the next year expressed strong intentions to use a rapid self-test, if available. A majority (87%) of MSM surveyed online in France were interested in self-tests, if available; interested men were more likely to have never tested or to have not tested in the past year, and to live their sex lives with men 'in absolute secrecy' [21]. The small proportion of the MSM (3.5%) in the study who had already accessed unapproved tests online had similar characteristics [22].…”
Section: Introductionmentioning
confidence: 92%